Role of liver function test parameters in acute appendicitis and its complication: a prospective study - Mishra, Braja Mohan; Nayak, Malaya Krishna; Mishra, Sandeep; Sahu, Priyambad; Das, Dibyajyoti (International Surgery Journal, 2018)
Background: Although acute appendicitis is the most common surgically correctable cause of abdominal pain, the diagnosis is challenging. There may not be classical symptoms and signs of appendicitis always. Accurate diagnosis can be aided by biochemical testings and radiological evaluation and expectant management. These might delay laparotomy and lead to complications of appendicitis and increase the morbidity. Recent research literatures have shown that hyperbilirubinemia is a diagnostic tool for gangrenous/perforation of appendix. This study is designed to evaluate the association between the derangement of liver function test and severity of acute appendicitis and it’s complications like gangrene and perforation of appendix. Methods: This was an observational prospective study on 66 consecutive cases of acute appendicitis done in the department of general surgery, VIMSAR, Burla. After taking informed consent, all patients included in the study were subjected to abdominal ultrasound and blood sample taken for routine blood examination, LFT and after appendicectomy histopathology examination report were collected. A master chat prepared from above data and stastical analysis done. Results: The LFT parameters are deranged in pathological appendix and more specifically the total bilirubin level but the sensitivity, specificity and PPV are specifically high for gangrenous and perforated appendix. Conclusions: LFT can be added as adjunctive test to the investigation of acute appendicitis and its complications and earlier diagnosis of the complications of acute appendicitis and timelier management. It can also help in prevention of negative appendicectomies.